Tuberculous meningitis: reducing the burden of disease by improving diagnosis and treatment - Heemskerk, A (2016)
Notwithstanding available diagnosis and treatment, tuberculosis (TB) is the most persistent pandemic known to modern man. Of all forms of tuberculosis, tuberculous meningitis (TBM) is the most lethal. The true burden of disease is unknown, but of the people who reach treatment facilities, approximately 30% die, despite therapy. The onset of disease is insidious and diagnosis is often only made after neurological compromise, a factor associated with increased mortality. Diagnosis is further complicated by lack of sensitivity of currently available conventional microbiological techniques. Moreover, recommended treatment regimens are derived from pulmonary TB regimens and not specifically adjusted to treat the infection in the brain, thus neglecting the differential ability of antimycobacterial drugs to cross the blood-brain barrier (BBB). Similarly, drug resistant infection is mostly detected late, because it depends on culture confirmation of this slow growing organism and optimal treatment regimens are unknown. In the context of intracranial infection, drug resistance is even more precarious, with high rates of mortality reported. This thesis addresses these pressing issues of diagnosis and treatment of TBM. The overarching aims of the studies performed in this thesis are: 1. To improve diagnosis of TBM by evaluating the performance of a novel molecular diagnostic test; Xpert MTB/RIF, 2. To improve treatment of TBM by evaluating an intensified antituberculosis treatment regimen. 3. To improve management of drug resistant TBM by exploring factors associated with drug resistance and evaluating response to intensified treatment. The Xpert MTB/RIF test was able to rapidly confirm a diagnosis of TBM with a sensitivity of 59.3% (n=108/182 (95% confidence interval(CI): 51.8-66.5)) compared to clinical diagnosis of TBM. Specificity was 99.5% (95% CI: 97.2-100). Particular advantages are the high sensitivity of the test in HIV positive patients and early detection of rifampicin resistance. Among HIV co-infected patients, sensitivity was 78.8% (n=52/66, (95% CI: 77.6-79.7)). Xpert MTB/RIF performance compared favourably with performance of commonly used classical staining techniques in most settings (1- 6 60%). This represents a significant advance in the early diagnosis of TBM and in particular of rifampicin resistance, which is considered a key drug in treatment regimens. Intensified antituberculosis treatment with higher dose rifampicin (15mg/kg) and additional levofloxacin, however, did not improve outcome in our cohort of 817 HIV infected (n=349) and uninfected (n=468) TBM patients. 113 and 114 patients died in the intensified treatment and placebo arm respectively (hazard ratio(HR), 0.94; 95% CI: 0.73 -1.22, p=0.66). Overall 9-month mortality was 28%, which is still unacceptably high. Predictors of death are HIV infection, disease severity grade on presentation and infection with multidrug resistant (MDR) mycobacteria, defined as at least resistance to rifampicin and isoniazid. The overall mycobacterial resistance rate found in this population was high; 45% of isolates showed resistance to at least one of four first line antituberculosis drugs, 27% were isoniazid resistant and MDR was detected in 5%. Patients with drug resistant infection did not have different presenting symptoms, but were more likely to have a history of previous TB treatment. Early intensified treatment did appear to be beneficial to outcome, in particular in HIV uninfected patients with isoniazid resistance (HR 0.11; 95%CI: 0.01-0.91, p=0.04). Of the 15 patients with MDR TBM, early detection of rifampicin resistance by Xpert MTB/RIF led to a successful early switch to second line therapy in four patients, who all survived up to nine months of follow up. In previous studies, prior to the availability of Xpert testing and secondline drugs, MDR TBM was uniformly lethal. Early diagnosis and treatment with effective antituberculosis drugs remains the most crucial aspect of management of this devastating condition.